Reviewer Acknowledgements for Journal of Agricultural Studies, Vol. 10, No. 2 - Williams, Richard (Journal of Agricultural Studies, 2022)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 10, Number 2 Alessandra M. Lima Naoe, Federal University of Tocantins, Brazil Alexandru Ioan Apahidean, Univ. of Agricultural Sci.&Veterinary Medicine, Romania Anca-Luiza Stanila, ICPA, Romania André Luiz Rodrigues Magalhães, UFAPE, Brazil Angel Ramon Sanchez Delgado, Universidade federal Rural do Rio de Janeiro, Brazil Arnaud Z. Dragicevic, IRSTEA, France Benard Kiplangat Rop, University of Nairobi, Kenya Darwin Pangaribuan, University of Lampung, Indonesia Eben von Well, Agricultural Research Council, South Africa Eric Owusu Danquah, CSIR-Crops Research Institute, Ghana Hedayatollah K. Soureshjani, Ferdowsi University of Mashhad, Iran Nkemkanma Vivian Agi, Rivers State University Port Harcourt, Nigeria Radu Liviu Sumalan, University of Agricultural Sciences and Veterinary, Romania Raul Pașcalău, Banat's University, Romania Sybelle Mesquita Silva, Universidade Federal de Alagoas, Brazil Richard Williams Editorial Assistant Journal of Agricultural Studies -------------------------------------- Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org